Chapter Introduzione - Senatore, Francesco (Reti Medievali E-Book, 2021)
The paper introduces the volume, focuses the purposes of the research, summarizes the essays and their historiographical framework. If you study the archives of Southern Italy's feudal lords, you are studying the nature of seigniorial power and the strategies of the aristocratic memory.